Kelulut honey improves folliculogenesis, steroidogenic, and aromatase enzyme profiles and ovarian histomorphology in letrozole-induced Polycystic Ovary Syndrome Rats - Mohd Kamal, Datu Agasi; Ibrahim, Siti Fatimah; Ugusman, Azizah; Mohamad Zaid, Siti Sarah; Mokhtar, Mohd Helmy (Multidisciplinary Digital Publishing Institute, 2022)
Polycystic ovary syndrome (PCOS) has been linked to aberrant folliculogenesis and abnormalities in the aromatase enzyme (Cyp19a1) and the steroidogenic enzyme, 17-alpha-hydroxylase (Cyp17a1) expression. It has been demonstrated that Kelulut honey (KH) improves both female and male reproductive system anomalies in animal studies. Here, we examined the effects of isolated and combined KH, metformin, and clomiphene in improving folliculogenesis, aromatase, and steroidogenic enzyme profiles and ovarian histomorphology in letrozole-induced PCOS rats. Letrozole (1 mg/kg/day) was administered to female Sprague–Dawley (SD) rats for 21 days to induce PCOS. PCOS rats were subsequently divided into six experimental groups: untreated, treatment with metformin (500 mg/kg/day), clomiphene (2 mg/kg/day), KH (1 g/kg/day), combined KH (1 g/kg/day) and metformin (500 mg/kg/day), and combined KH (1 g/kg/day) and clomiphene (2 mg/kg/day). All treatments were given orally for 35 days. We found that KH was comparable with clomiphene and metformin in improving the expression of Cyp17a1 and Cyp19a1, apart from enhancing folliculogenesis both histologically and through the expression of folliculogenesis-related genes. Besides, the combination of KH with clomiphene was the most effective treatment in improving the ovarian histomorphology of PCOS rats. The effectiveness of KH in restoring altered folliculogenesis, steroidogenic, and aromatase enzyme profiles in PCOS warrants a future clinical trial to validate its therapeutic effect clinically.